A study on the surface quality of the 3D printed parts caused by the scanning strategy. Issue 2 (4th March 2019) - Han, Jitai; Ge, Yanan; Mao, Yuxin; Wu, Meiping
Abstract : Purpose: The purpose of this paper is to mainly focus on the relationship between the scanning strategy and surface quality. Surface quality, including surface roughness and flatness, is important for printed parts. So this paper optimizes the surface quality by changing the scanning strategy. Design/methodology/approach: This paper is based on the phenomenon after the printed parts. A clear trend can be seen that the surface roughness on the side face shows a clear zigzag shape, so an optimized scanning strategy is used. Surface roughness in measured in macrostructure first by Mitutoyo and the flatness is measured by Hexagon Metrocogy. After that, microstructure on the side face is seen by RTEC to explain this phenomenon. Findings: The surface quality on the side face shows a significant optimize by changing the scanning strategy. The surface quality on the positive face has some optimization to some degree. Originality/value: This paper determines the relationship between the surface roughness on the side face and the scanning strategy. Few studies focus on the surface roughness, especially on the side face. Some studies try to optimize the surface roughness on the positive face. However, researchers always neglect the surface roughness on the side face. 2. This paper measures not only the surface roughness, but also the flatness. Surface roughness has a significant impact on the surface quality. However, it still has some limitations. Flatness is also measured to make this paper more representative. 3. This paper explains why scanning strategy can affect the surface quality. These images explain the research better and not just at the theoretical level.